"True and fair view" : an empirical study of the perceptions of managers. - Goh, Kien Hwee. (2013)
The "True and Fair View” (TFV) debate has been ongoing for decades. First seen in the UK Companies Act 1948, the TFV concept has since been incorporated into various colonial statutes, and recently, the European Community Judiciary. There has yet been a concrete definition of this term. The ambiguous nature of the words"true and fair” has resulted in a call for a more useful definition. Some even proposed other terms, Hke Generally Accepted Accounting Principles (GAAP), to serve as the accounting standard.